1995
DOI: 10.1002/prot.340210305
|View full text |Cite
|
Sign up to set email alerts
|

A model for the LexA repressor DNA complex

Abstract: A structural model for the interaction of the LexA repressor DNA binding domain (DBD) with operator DNA is derived by means of Monte Carlo docking. Protein-DNA complexes were generated by docking the LexA repressor DBD NMR solution structure onto both rigid and bent B-DNA structures while giving energy bonuses for contacts in agreement with experimental data. In the resulting complexes, helix III of the LexA repressor DBD is located in the major groove of the DNA and residues Asn-41, Glu-44, and Glu-45 form sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 29 publications
6
39
0
Order By: Relevance
“…1) reveals that the Alphaproteobacteria LexA protein possesses a 33 amino acid insertion downstream of the predicted third helix (a3) of its binding domain that is not seen in any other bacterial group. This gives further credence to the direction of the LGT deduced from the LexA tree, and also supports the hypothesis that this insert does not affect the DNA binding domain (DBD) (Knegtel et al, 1995).…”
Section: Discussionsupporting
confidence: 77%
“…1) reveals that the Alphaproteobacteria LexA protein possesses a 33 amino acid insertion downstream of the predicted third helix (a3) of its binding domain that is not seen in any other bacterial group. This gives further credence to the direction of the LGT deduced from the LexA tree, and also supports the hypothesis that this insert does not affect the DNA binding domain (DBD) (Knegtel et al, 1995).…”
Section: Discussionsupporting
confidence: 77%
“…This fact suggests that these residues must also be related to structural functions of the LexA helix-turn-helix (HTH) complex rather than to the specific recognition of the DNA-binding sequence. It has been suggested that, in E. coli, the third a helix of the LexA HTH complex plays the leading role in specific DNA recognition (Knegtel et al, 1995). However, other residues in the remaining a helices or between them must also play a significant part in specific DNA recognition, since a F. succinogenes LexA protein derivative in which the sequence of the third a helix has been replaced through directed mutagenesis with that of E. coli LexA can not bind the E. coli-like CTGTN 8 ACAG motif (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…So far, all the identified and characterized LexA proteins display two conserved domains that are clearly differentiated. The N-domain, ending at the Ala-Gly bond where the protein is cleaved after DNA damage activation of RecA (Little, 1991), has three a helices that are necessary for the recognition and binding of LexA to the SOS box (Fogh et al, 1994;Knegtel et al, 1995). Conversely, the C-domain contains amino acids that are essential for the serine-protease-mediated auto-cleavage and for the dimerization process necessary for repression (Luo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…1). Intact LexA dimerises by the carboxyterminal domain (CTD) [37,42], and binds to DNA sequences via a helix-turn-helix in its amino-terminal domain (NTD) [43]. The three-dimensional structure of the LexA-NTD has been solved by NMR spectroscopy (pdb ID: 1lea) [44] and, subsequently, the crystal structures of fulllength mutant forms of LexA were reported [37].…”
Section: E Coli Lexa Monomermentioning
confidence: 99%
“…However, biochemical and biophysical methods have been used to investigate the specific contacts made by E. coli LexA NTD upon binding at targets [38, 39, 41, 62, 77 -79] and a structural model has been generated [43] by docking the NTD NMR solution structure (average of pdb ID: 1leb) onto DNA (Fig. 2B).…”
Section: Establishing Specific Dna Bindingmentioning
confidence: 99%